The evolution of settlement areas of Ingrian Finns in Northwest Russia in the second half of the 20th century - Stupin, Yu. (RUS, 2017)
Based on the nation-wide censuses conducted between 1959 and 2010 in the Soviet Union and in the Russian Federation, as well as on the contemporary data of the Estonian Department of Statistics, the author of this article studies the spatial aspects of the dynamics of the ethnic area of Ingrian Finns within their main settlement area. This is done through utilizing ethnicity-related statistical data of the district at the lowest level of administrative division. The author emphasises a significant increase in the rates of degradation of the Ingiran settlement area in the post-Soviet period, identifies the factors behind it, and considers district differences in the rates of depopulation and assimilation of the Russian Finns. The results of research make it possible to foreground and describe in detail the available information on the spatial organisation of Russian Finnish population in the North-western region of Russia.